The Relationship Between Parenting Stress and Social Skills of Preschool Children - Han, Yuting; Eng Hock, Kway (South Asian Journal of Social Sciences and Humanities, 2023)
Social skills refer to specific task-related behaviors in daily life, such as participating in peer  interactions, making friends, or making requests. In early childhood, social skills have a  significant impact on their future academic performance, behavior patterns and even mental  health. In this quantitative study, a questionnaire survey was conducted, selecting samples  from urban kindergartens in Heze City, Shandong Province, China, and collecting a total of  256 valid questionnaires. The results showed that preschoolers' social skills (2.69±0.34, 2.5  is the mean score) were at a medium level and parents' parenting stress (2.34±0.60, 3 is the  mean score) were at a medium to low level. Children's social skills differed significantly on  the mother's education variable but not on other demographic variables. Children whose  mothers' education was undergraduate had better social skills than children whose mothers'  education was college, and children whose mothers' education was postgraduate had better  social skills than children whose mothers' education was college. There is a significant and  negative correlation between children's social skills and parents' parenting stress (correlation  coefficient = - 0.171**), and parents' parenting stress was predictive of children's social skills (β= - 0.143). This study may contribute to designing social skills intervention programs for  preschool children from the parents' perspective and expand research considerations on social  skills interventions.
Keywords: parents; parenting stress; preschool children; social skills